Fabrication of nitrogen and sulfur co-doped hollow cellular carbon nanocapsules as efficient electrode materials for energy storage - Zhu, Qi-Long; Pachfule, Pradip; Strubel, Patrick; Li, Zhangpeng; Zou, Ruqiang; Liu, Zheng; Kaskel, Stefan; Xu, Qiang (Energy Storage Materials, 2018)
Hierarchical hollow carbon materials are attracting considerable attention because of their unique structural characteristics, extraordinary electrical and thermal properties. Here, we present the fabrication of N and S co-doped hollow cellular carbon nanocapsules with high surface area and pore volume from a metal–organic framework composite by a facile external template-free method. The unique nanocapsules feature large internal hollow cores, hierarchical porous cellular shells with ultrathin walls of a few nanometers thickness, and uniform N and S co-doping, which enable an efficient supercapacitor behavior by enhancing the diffusion of electrolyte ions and providing large accessible active surface. The combination of the optimal pore structure and surface functionality of the resulting materials affords an excellent capacitive performance with high specific capacitances and energy densities in both aqueous and non-aqueous media.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Carbons; Doping; Metal–organic frameworks; Nanocapsules; Supercapacitors